Agricultural Management Options for Climate Variability and Change: Variable-Rate Irrigation - Calvin Perry; Clyde Fraisse; Daniel Dourte (EDIS)
Most fields are not uniform because of natural variations in soil type or topography. When water is applied uniformly to a field, some areas of the field may be overwatered while other areas may remain too dry. Variable-rate irrigation technology gives farmers an automated method to vary rates of irrigation water based on the individual management zones within a field and avoid irrigating roadways, waterways, wetlands, and other non-farmed areas within a pivot. This 3-page fact sheet was written by Calvin Perry, Clyde Fraisse, and Daniel Dourte, and published by the UF Department of Agricultural and Biological Engineering, July 2012.